Conexões entre o comum urbano, cultura política e território nas ocupações Alto Bonito e Jardim Deus é Fiel em Araguaína - TO - Pinto, Sandro Ferreira (2021)
This is a research on two urban occupations for housing purposes – Alto Bonito and Jardim Deus é Fiel, both located in Araguaína - TO. We studied, along with the communities, their practices in the search for theoretical and empirical ties with the urban Common, investigating it as a political principle and as a biopolitical production. In summary, our research problem consists of investigating traits of the common in the occupations surveyed, specifically in territorialization practices. We lean over theoretical elaborations of the Common and the urban Common, dialoguing with other relatable theoretical strands, seeking references in Foucault (2008; 2008.b; 2019; 2019; 2019.b) and Agamben (2002; 2016; 2017; 2019) for better understand the categories of biopower, biopolitics and bare life. Afterwards, we established the central authors of the investigation of the Common, Hardt and Negri (2014; 2016; 2018), Dardot and Laval (2018), following the path already paved by João Bosco de Moura Tonucci Filho (2017; 2020), we dedicated ourselves to the urban in the perspective of Lefebvre (2002; 2011; 2013) in order to establish a theoretical basis to understand the Urban Common in the aforementioned neighborhoods. In another part, we seek to bring concepts of political culture and territory capable of conversing with the articulation of the urban Common. At the end, we looked in the field of research, in community experiences, for elements of connection between the theoretical background, namely, Urban common, political culture and territory. Our focus was limited to activities related to the installation and maintenance of occupations, access to electricity and potable water service networks, and resistance and defense actions in the face of the constant risk of eviction. The study was developed in conjunction with the community and concurrently with the research, we continued in the technical defense of the occupants with the repossession actions. The methodology chosen for the work was the action research, as it is more consistent with this mutual involvement between researchers and the field and adequate for the proposed purposes – helping to maintain the occupants in the occupied area. By the end, we were able to verify theoretical traits of the urban common and of the territory in the practices studied, but not without considerations and adjustments between the theory present in the bibliographic instruments used and the peripheral Brazilian experiences researched.